The Siloam Tunnel inscription. Historical and linguistic perspectives - Rendsburg, Gary A. (Israel exploration journal, 2010)
The present article seeks to answer two questions: a) who the builders of the Siloam Tunnel were; and b) how one explains the three linguistic peculiarities of the relatively short Siloam Tunnel inscription. The historical, archaeological and linguistic evidence suggest that the tunnel was constructed by individuals who emigrated to Jerusalem from southern Samaria (Ephraim) and Benjamin in advance of the Assyrian invasion of the land. At least three—if not four—linguistic features in the inscription are associated with the Hebrew dialect of this border region, straddling the domains of the kingdom of Israel to the north and the kingdom of Judah to the south. This finding, in turn, suggests that a literate individual from within the group of builders was responsible for the epigraph.